2022
DOI: 10.1021/acsami.1c19665
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanoarchitectonics with Bi Nanoparticle Encapsulation for Improved Electrochemical Deionization Performance

Abstract: Electrochemical deionization (EDI) is hopefully the next generation of water treatment technology. Bismuth (Bi) is a promising anode material for EDI, due to its high capacity and selectivity toward Cl–, but the large volume expansion and severe pulverization aggressively attenuated the EDI cycling performance of Bi electrodes. Herein, carbon-layer-encapsulated nano-Bi composites (Bi@C) were prepared by a simple pyrolysis method using a Bi-based metal–organic framework as a precursor. Bi nanoparticles are unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The C 1s spectra in Figures d and S2 show a main CC peak, coexisting with three weak peaks of C–O, CO, and O–CO. The existence of the CC bond improves the conductivity of the Bi⊂CM composites . The Bi 4f spectra exhibit two peaks at binding energies of 159.3 (Bi 4f 7/2 ) and 164.6 eV (Bi 4f 5/2 ), which are indexed to Bi 2 O 3 that is oxidized from Bi metal in the composites .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The C 1s spectra in Figures d and S2 show a main CC peak, coexisting with three weak peaks of C–O, CO, and O–CO. The existence of the CC bond improves the conductivity of the Bi⊂CM composites . The Bi 4f spectra exhibit two peaks at binding energies of 159.3 (Bi 4f 7/2 ) and 164.6 eV (Bi 4f 5/2 ), which are indexed to Bi 2 O 3 that is oxidized from Bi metal in the composites .…”
Section: Resultsmentioning
confidence: 97%
“…The existence of the C�C bond improves the conductivity of the Bi⊂CM composites. 32 The Bi 4f spectra exhibit two peaks at binding energies of 159.3 (Bi 4f 7/2 ) and 164.6 eV (Bi 4f 5/2 ), which are indexed to Bi 2 O 3 that is oxidized from Bi metal in the composites. 25 This was also reflected by the Bi−O−Bi bond in the O 1s spectra, in which the peak at 532.3 eV could be assigned to the Bi−O−C bond in the Bi⊂CM composites.…”
Section: Resultsmentioning
confidence: 99%
“…Capacitive deionization (CDI) is a robust process for producing clean water from brackish water with low energy input and high efficiency. The most important part of CDI is the electrode, which determines the desalination performance. In recent years, CDI faradic electrodes emerged as a hot topic due to their strong deionization ability. While several materials have been explored for the selective removal of sodium (Na + ) ions, faradic materials for the removal of chloride (Cl – ) ions are limited . Materials like Ag and Bi, which are often used for Cl – capture, face challenges like high costs and poor cycle performance. , …”
Section: Introductionmentioning
confidence: 99%
“…Besides, co-ion expulsion often occurs, leading to a significant decrease in charge efficiency and an increase in energy consumption. To overcome the limitations, Faraday electrode materials based on reversible redox reactions or ion intercalation effects are studied . It has been shown that the Faraday electrode materials selectively adsorb cations or anions, avoiding the co-ion expulsion effect and increasing desalination charging efficiency .…”
Section: Introductionmentioning
confidence: 99%